The Influence Of Managerial Competence And Democratic Leadership Style On School Quality Mediated By School-Based Management In Sukakerta 03 Public Schools - Ikhwan Nur Ismail; Taufiq Rachman; Adibah Yahya (Dinasti International Journal of Education Management And Social Science, 2024)
This study examines the effect of managerial competence and democratic leadership style on school quality, mediated by school-based management at SDN Sukakerta 03. The phenomenon of the problem at hand is the low quality of education in Indonesia, which is reflected in the 2018 PISA survey results. The purpose of this study is to analyze how much influence managerial competence and democratic leadership style have on school quality, taking into account the mediating role of school-based management. The method used is quantitative with path analysis to test the research hypothesis. Data were collected through questionnaires distributed to teachers at SDN Sukakerta 03. The results showed that managerial competence and democratic leadership style have a significant influence on school quality. School-based management was also shown to mediate the relationship between managerial competence and school quality, as well as between democratic leadership style and school quality. However, this mediating effect was not statistically significant. In conclusion, improving managerial competencies and implementing democratic leadership styles can improve school quality, although the mediating role of school-based management needs further attention.